Comparing readiness for self directed learning in undergraduates of private and public medical colleges - Javaria Ahmad; Fatima Izhar Mehdi; Manal Fatima Cheema; Minahil Aftab; Zainab Omer (Journal of the Pakistan Medical Association, 2024)
Objective: To measure the readiness for self-directed learning among medical undergraduates of private and public medical colleges, and to evaluate their performance and strategies. Method: The cross-sectional study was conducted in Lahore, Pakistan from February to July 2023, and comprised medical undergraduate students of either gender from 1 private and 1 public academic institution. Data was collected using a pre-validated structured questionnaire having self-management, desire for learning, and self-control domains to explore self-directed learning readiness. Data was analysed using SPSS 26. Results: Of the 330 subjects, 166(50.3%) were females and 164(49.7%) males, while 166(50.3%) were from the private institution and 164(49.7%) were from the public institution. There were 183(55.4%) students in the 3rd year, 89(27.0%) in the 4th year and 58(17.6%) in the final year of their coursework. Self-directed learning readiness was significantly higher in students from the private institution (p<0.05). Conclusion: There was a significant correlation between self-directed learning readiness in private and public medical education institutions, with readiness being higher in the private sector. Key Words: Self-directed learning, Self-control, Experiential learning, Problem-based learning, Active learning.